Biochar production from agriculture waste to enhance crop yield and fertilizer application - Suganthi a/p Sudarman (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
As the world is developing, the waste from industrial is increasing as well. Agriculture waste is one of the severe industrial wastes that have been produced. The objective of the project was converting agriculture biomass waste such as saw dust, coconut dreg and rice straw to stable biochar via pyrolysis and subsequently add this biochar to soil for crop production. Biochar is proposed to act not only as carbon sink but also as adsorbent for organic and inorganic fertilizer thus improving crop yield and reduced the fertilizer usage. First part of the study was about the effects of pyrolysis condition particularly temperature, on elemental composition, pH, ash content, moisture content and adsorption study. From the experiment we can obtain that low temperature (450 C) can yield a high biochar yield. The pH reading of biochar was more than 7. Saw dust 8.10, coconut dreg 9.34 and rice straw 10.87. While the ash content in rice straw biochar 44 % would be higher than the other two samples. The moisture content of saw dust 14.60 %, rice straw 14 % and coconut dreg 13.40 %. Besides that the adsorption capacity high in saw dust than the other two samples. Another part of the study involved an easy growing plant which has been used to investigate the yield of crop by using the biochar. Twelve plants was planted and observed the condition of each plant. Nine pots of plant which contain three different type biochar samples and another three pots without any biochar in the pots. The plants in the pots that have biochar grow healthier, weightier and taller. The root of the plant with biochar is much longer than without the biochar pot. The height of the plant in saw dust biochar is 33.72 cm, the root length 14 cm and dry weight is 203 g, coconut dreg 31.20 cm, 12.17 cm and 195 g, rice straw 30.23 cm, 11.23 cm and 191 g, and control pot 25.23 cm, 8.40 cm and 151 g.